Mental health among immigrants in Germany - the impact of self-attribution and attribution by others as an immigrant - Yuriy Nesterko; Michael Friedrich; Elmar Brähler; Andreas Hinz; Heide Glaesmer (BMC, 2019)
Abstract Background In Germany, the term 'migration background' has been established to differentiate between immigrants and natives. In the present study post-traumatic stress disorder (PTSD), anxiety, and depression were analysed in immigrant populations in Germany by considering self-attribution as well as attribution by others on one's own 'migration background'. Methods In a population-based survey (N = 2317), socio-demographic characteristics, migration background (official statistics definition vs. self-attribution as well as the anticipated attribution by others), PTSD (PCL-5), and symptoms of anxiety and depression (PHQ-4) were assessed. Logistic regression models were applied to predict mental health outcomes by considering socio-demographic and immigration-related factors. Results A total of 10.7% of respondents (N = 248) had a 'migration background'. Immigrants of the 2nd generation compared to 1st generation immigrants are less likely to see themselves as immigrants. Attribution as an immigrant (self and/or by others) was found as significant predictor for PTSD and depression, but not anxiety. Conclusions It seems useful to focus on immigration-related factors considering subjective perspectives and not only comparing immigrants and natives using a federal statistics definition. Our findings suggest that research on the association between immigration-related factors such as attribution as an immigrant and mental health outcomes might be a promising approach to better identify subgroups at higher risk of mental distress.